2017
DOI: 10.12688/f1000research.10817.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding and managing cancer pain

Abstract: Cancer pain remains a significant clinical problem worldwide. Causes of cancer pain are multifactorial and complex and are likely to vary with an array of tumor-related and host-related factors and processes. Pathophysiology is poorly understood; however, new laboratory research points to cross-talk between cancer cells and host’s immune and neural systems as an important potential mechanism that may be broadly relevant to many cancer pain syndromes. Opioids remain the most effective pharmaceuticals used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
73
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 97 publications
0
73
0
2
Order By: Relevance
“…2 For these patients, health care providers (HCPs) prescribe oxycodone, morphine, fentanyl, and other opioid analgesics, which are highly effective for alleviating cancer-related pain. 3,4 However, gastrointestinal (GI) side effects are common with these drugs because they stimulate peripheral m-opioid receptors in the GI tract, resulting in delayed gastric emptying, oral-cecal transit, and colonic transit. 5 Opioidinduced constipation (OIC) is the most common GI side effect of opioid therapy, resulting in the discontinuation of opioid treatment or reduction in opioid dose, compromising effective pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…2 For these patients, health care providers (HCPs) prescribe oxycodone, morphine, fentanyl, and other opioid analgesics, which are highly effective for alleviating cancer-related pain. 3,4 However, gastrointestinal (GI) side effects are common with these drugs because they stimulate peripheral m-opioid receptors in the GI tract, resulting in delayed gastric emptying, oral-cecal transit, and colonic transit. 5 Opioidinduced constipation (OIC) is the most common GI side effect of opioid therapy, resulting in the discontinuation of opioid treatment or reduction in opioid dose, compromising effective pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…This pain can last for months to years or even persist throughout a lifetime, with adverse impacts on functioning and quality of life . While nonopioid measures alone can often treat mild cancer‐related pain, opioids may be needed for treating more severe pain . However, there have been growing concerns regarding long‐term opioid therapy in older cancer survivors, in part due to the worsening epidemic of opioid toxicity in the United States …”
mentioning
confidence: 99%
“…[6][7][8] While nonopioid measures alone can often treat mild cancerrelated pain, opioids may be needed for treating more severe pain. 4,9,10 However, there have been growing concerns regarding long-term opioid therapy in older cancer survivors, in part due to the worsening epidemic of opioid toxicity in the United States. 6,10,11 Past research has shown that long-term opioid therapy is a known risk factor for opioid-related toxicities, including opioid dependence, overdose, falls, fractures, and premature death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding cancer pain through this approach is a major key to provide an optimal management for our patients with cancer pain. Rather than a step-wise approach, this exhaustive pain medicine leads to multimodal and personalized responses, by associating interventional and integrated complementary approaches to current therapeutics strategies [4][5][6][7][8][9], and beyond, opening the way to supportive medicine in a simple, integrative, dynamic patients' management model. Integrating supportive medicine to cancer and serious chronic diseases pathway can be a key operational response, in parallel to the constant hyperspecialization of medicine.…”
mentioning
confidence: 99%